The Application of Expert System in Diagnosing Catfish Diseases Using Forward Chaining Method - Afdal, Muhammad; Melladia (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
Indonesia, as an archipelagic nation, holds significant potential for the development of freshwater commodities, particularly catfish. Catfish farming is feasible in limited spaces but is susceptible to various diseases, resulting in substantial losses for farmers. This study aims to develop an expert system based on the forward chaining method, designed to diagnose catfish diseases according to observed symptoms and provide treatment solutions without requiring direct expert consultation. A qualitative approach was employed, with data collected through literature reviews and expert interviews. The developed expert system was implemented using MATLAB to generate accurate diagnoses and treatment recommendations. The results show that the system can accurately recognize different types of catfish diseases based on the symptoms provided. It also gives suitable treatment options, helping farmers learn about the disease, its symptoms, and the right ways to treat it. This makes farming more efficient and reduces the damage caused by diseases.